Aquaporins in metabolic syndrome : new targets for drug discovery - da Silva, Inês V. (2022)
Obesity is one of the most important metabolic disorders of this century and is associated with a cluster of the most dangerous cardiovascular disease risk factors, such as insulin resistance, diabetes, dyslipidaemia and hypertension, collectively named Metabolic Syndrome. With the discovery of aquaporins (AQPs, membrane protein channels that facilitate water permeation through membranes) new targets for drug development influenced the research in this field. For now, thirteen aquaporins have been described in humans, whose isoforms 3, 7, 9 and 10 are subcategorized as aquaglyceroporins allowing both water and glycerol transport. The role of aquaporins in glycerol metabolism, facilitating glycerol release from the adipose tissue and distribution to various tissues and organs, unveils these membrane channels as important players in lipid balance and energy homeostasis and points to their involvement in a variety of disorders including insulin resistance, obesity and diabetes. The thesis introduction (Chapter 1) gives an overview on Metabolic Syndrome and Obesity and introduces several structural and physiological aspects of aquaporins that make these proteins potential targets in the context of metabolic health and disease. This chapter describes the aquaporin family and structure, their main biological functions and related pathologies, with special emphasis on aquaglyceroporins and their role as glycerol channels. The first part of this thesis (Chapter 2), is dedicated to the involvement of several mammalian aquaporin isoforms (with focus on aquaglyceroporins) in various obesity-related pathologies, using different types of cells (endothelial cells, pancreatic β-cells and macrophages) as models of study. Using molecular, biochemical and biophysical techniques, we were able to disclose the involvement of aquaporin isoforms in metabolic-related complications, such as endothelial dysfunction, pancreatic β-cell inflammation and inflammasome activation in macrophages. In the second part of this thesis (Chapter 3), AQP3 genetic polymorphisms analysis showed to be a potential tool to predict hypertension. In this study, the analysis of aquaporin isoforms (AQP3 and AQP7) polymorphisms and other relevant hypertension-related gene polymorphisms were evaluated along with biochemical parameters, in a well characterized cohort of pregnant women that were then followed-up for several years, and were found related to the development of preeclampsia and/or future hypertension. In the third part of this thesis (Chapter 4), the transcriptional profile of adipose aquaporins (aquaglyceroporins AQP3 and AQP7; orthodox aquaporin AQP5) was assessed in white (subcutaneous and visceral) and brown adipose tissue of hamsters fed diets enriched in omega-3 fatty acids (n-3 long chain PUFA) in different lipid structures (triacylglycerol and ethyl ester). A correlation of AQPs differential expression with the type of n-3 lipid structure was found, with the adipose AQP7 showing a conservative role across WAT and BAT with highest targeting potential. In the last part of the thesis (Chapter 5), a general conclusion and final remarks unveil aquaporins as potential targets in the development of new therapies.